1995
DOI: 10.1111/j.1528-1157.1995.tb01670.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensory Event‐Related Potentials in Patients with Temporal Lobe Epilepsy

Abstract: We investigated chemosensory functions in patients with temporal lobe epilepsy (TLE) to discover whether olfactory and trigeminal stimuli applied either ipsilaterally or contralaterally to the epileptic focus are processed differently. Twenty-two patients were investigated, 12 of whom had epilepsy with a focus located in left temporal lobe (LTL). The remaining 10 patients had a right temporal lobe (RTL) focus. Input from the trigeminal system was examined by use of CO2; input from the olfactory system was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
21
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 32 publications
7
21
1
1
Order By: Relevance
“…In studies on patients with temporal lobe epilepsy, the results have been unclear as to whether a greater olfactory dysfunction occurs with left or right temporal lobe dysfunction. Support for the dominant role of right temporal lobe in olfactory function comes from studies by Jones-Gotman et al [9], Abraham et al [10], Hummel et al [11], and Zatorre et al [8], while other authors present favorable results for the equivalent relevance of both temporal lobes in olfactory function [12].…”
Section: Introductionmentioning
confidence: 92%
“…In studies on patients with temporal lobe epilepsy, the results have been unclear as to whether a greater olfactory dysfunction occurs with left or right temporal lobe dysfunction. Support for the dominant role of right temporal lobe in olfactory function comes from studies by Jones-Gotman et al [9], Abraham et al [10], Hummel et al [11], and Zatorre et al [8], while other authors present favorable results for the equivalent relevance of both temporal lobes in olfactory function [12].…”
Section: Introductionmentioning
confidence: 92%
“…Finally, trigeminal activation leads to activity in the insular cortex [68] and the ventral orbital cortex [60,100], with stronger right-sided activity following bilateral stimulation [43,60]. These areas have also been shown to be involved in the processing of olfactory information, and, similarly, research indicates that the right hemisphere is involved to a larger degree in the processing of information about odors [56,63,89,117,118].…”
Section: Basic Anatomy and Physiology Of The Intranasal Trigeminal Symentioning
confidence: 97%
“…More recently, Jones-Gotman et al [30] and Haehner et al [21] found poorer bilateral odor identification in TLR patients, with poorest performance on the resected side. Other investigators have found no differences between left- and right-side foci and/or resections on bilaterally-administered olfactory tests, including tests of identification, odor memory, and discrimination [9, 18, 19, 27, 29, 42, 49]. In the pre- and post-operative study by Martinez et al [32], odor discrimination was lower only following right-side resection, with improvement occurring on the left side.…”
Section: Introductionmentioning
confidence: 96%